2-Deoxyribose Gene-Enzyme Complex in Salmonella typhimurium I. Isolation and Enzymatic Characterization of 2-Deoxyribose-Negative Mutants - Hoffee, Patricia A. (1968)
Salmonella typhimurium was found to utilize 2-deoxyribose as a sole carbon and energy source. Cells grown in the presence of deoxyribose contained increased levels of deoxyribose kinase, thymidine phosphorylase, and two forms of deoxyribose-5-phosphate aldolase (DR5P aldolase). One form of DR5P aldolase was induced by deoxyribose and coordinately regulated with deoxyribose kinase. The second form of DR5P aldolase was induced by deoxyribose-5-phosphate and coordinately regulated with thymidine phosphorylase. Mutants unable to ferment deoxyribose have been isolated and shown to be lacking either deoxyribose kinase or deoxyribose permease, but none has been found from which DR5P aldolase is missing. Thymine-requiring mutants which are able to grow on low levels of thymine have been isolated and shown, in some cases, to be lacking one or both DR5P aldolases.